Pengaruh Learning Organizational dan Budaya Organisasi Terhadap Kepuasan Kerja Pegawai Badan Pusat Statistik Kabupaten Lampung Tengah - Haris Sugara; Iskandar Ali Alam (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The increasing demands for performance and the complexity of tasks in government institutions require organizations to manage human resources effectively. In this context, the implementation of a learning organization and a supportive organizational culture are important factors in enhancing employee job satisfaction. This study aims to analyze the effect of learning organization and organizational culture on the job satisfaction of employees at the Central Statistics Agency (Badan Pusat Statistik) of Central Lampung Regency. This research employs a quantitative approach using a survey method. The research population consists of all 40 employees of the Central Statistics Agency of Central Lampung Regency, with a saturated sampling technique applied. Data were collected through Likert-scale questionnaires and analyzed using multiple linear regression with the assistance of SPSS software. The results show that learning organization has a positive and significant effect on employee job satisfaction. Organizational culture is also proven to have a positive and significant effect on employee job satisfaction. Simultaneously, learning organization and organizational culture have a positive and significant effect on employee job satisfaction. These findings indicate that improving learning organization practices and strengthening organizational culture can enhance employee job satisfaction.